â€œTriggers and Spursâ€ of English Language Teaching at Junior High School in Yogyakarta - Avansa Naufal Hakim; Yuyun Yulia (Journal of English Language and Pedagogy, 2019)
This research is aimed at describing activities used to make the students enthusiastic to participate in English learning activities. It is a descriptive qualitative study involving four English teachers from two schools that have different characteristics in terms of school management. The first school is under Ministry of National Education (MONE) and another is under Ministry of Religion Affairs (MORA). The data gained are from observation, Focus Group Discussion (FGD), in-depth interview, and documentation. The findings of this research shows that the students were more delighted in learning when the teacher implemented exciting learning activities. Teachers used activities to make the students enthusiastic to participate in English learning activities and to make them spurred in learning English. The teacher triggered the students by implementing activities such as Near Peer Role Model (NPRM), Mingling Games and Tiered. As a result, students become spurred because the social interaction is involved.